Berinvestasi pada Reksadana Syariah ; Suatu Tinjauan Kritis - Muhamad Johari (TAFAQQUH, 2018)
Investment or asset placement either property or thing as a mean to result income or will increase value in the future known as investing. Return in an investment is influenced by the risks that accompany it. The greater return on offer, it mean is the greater  risk, and vice versa. Investments in mutual funds are suitable for novice investors, because it does not require huge funds, also the rate of return is better than saving. Along the improving investment climate and economy  in Indonesia, the tendency of society to invest tobe higher, especially in mutual funds. Mutual fund developments can be seen at NAV (net asset value), is one of the benchmarks for monitoring the outcome of a mutual fund. If the total NAV increase, that mean NAV per unit also increased, then the investor will earn huge profits. And if the total NAV decline, that mean the investor will suffer losses.